2022
DOI: 10.1002/hec.4609
|View full text |Cite
|
Sign up to set email alerts
|

Do sugar‐sweetened beverage taxes improve public health for high school aged adolescents?

Abstract: Sugar‐sweetened beverage taxes have become an increasingly popular policy to combat the worldwide obesity epidemic, but relatively little is known about their impact on health outcomes, particularly among high school aged students. In this paper, I use public‐use data from the Youth Risk Behavioral Surveillance System to determine whether high school students living in three of the American cities which have implemented Sugar‐sweetened beverage taxes have experienced public health improvements. Using an event‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Notably, our estimated unintended, adverse effects of lockdown on body weight outcomes are comparable to the unintended negative effects of other policies on body weight, for instance, cigarette taxes (Courtemanche, 2009). These effects might be even large enough to potentially offset the benefits of policy interventions aimed at reducing obesity, such as soda taxes (Flynn, 2023) and restaurant calorie labeling regulations (Aranda et al, 2021; Courtemanche et al, 2020; Restrepo, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, our estimated unintended, adverse effects of lockdown on body weight outcomes are comparable to the unintended negative effects of other policies on body weight, for instance, cigarette taxes (Courtemanche, 2009). These effects might be even large enough to potentially offset the benefits of policy interventions aimed at reducing obesity, such as soda taxes (Flynn, 2023) and restaurant calorie labeling regulations (Aranda et al, 2021; Courtemanche et al, 2020; Restrepo, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The search intensity for "Uber Eats" even appears to rise again after 6 months post-lockdown. Existing evidence suggests that increased access to online food delivery may promote unhealthy dietary habits by expanding access to highly processed foods (Fernandez & Raine, 2021), potentially contributing to the increase in body weight observed post-lockdown (Babar et al, 2021).…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Our findings are consistent with those of previous studies. Flynn 17 investigated the combined areas of Philadelphia, San Francisco, and Oakland and reported an average decrease in children’s BMI from before to after beverage taxes were implemented. Additionally, a study from Mexico 16 reported an association between Mexico’s tax and decreased BMI among girls.…”
Section: Discussionmentioning
confidence: 99%
“…In the second study, investigators found that pass-through of the Mexico sweetened beverage tax was associated with a reduction in obesity prevalence among adolescent girls, but not boys . The third study examined sweetened beverage taxes in 3 cities (Philadelphia, Pennsylvania; San Francisco, California; and Oakland, California), and beverage taxes were associated with a decrease in average BMI among all children, but with larger effects among girls . Each of these studies used repeated cross-sectional samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation